Evaluation of the effect of fortified and concentrated hay supplementation on the production of bovine milk (Bos taurus L.) during the dry season in the Achaca-Tiahuanacu community - Patty-Quispe Magda Hortencia; Loza-Murguia Manuel Gregorio; Achu-Nina Cristóbal; Rojas-Pardo Abel; Chura-Limachi Felipe; Quispe-Paxipati Cesar Humberto (Journal of the Selva Andina Animal Science, 2017)
The present study was carried out in the Achaca Community of the Municipality of Tiahuanacu, with the objective of evaluating the effect of supplementation with fortified and concentrated hay on milk production, feed conversion, total solids and production costs in three periods (Control, adaptation and supplementation) during the dry season (October and November). 12 Holstein mestizo cows were used between 4 and 6 months of lactation. The design used was completely randomized blocks with factorial arrangement of 2Ax3Bx (3) with three replicates. The average milk yield of 4.69 kg of cows supplemented with fortified hay and 6.24 kg with concentrate were higher than the production of 3.94 and 5.11 kg respectively in the adaptation period and finally the production of 3.58 and 3.42 kg in the control period. The feed conversion with fortified hay supplementation of 2.60 kg was greater than 2.12 and 1.90 kg respectively. While feed conversion between supplements was 1.61 and 1.78 kg with concentrate in the adaptation period and finally with 2.12 and 2.60 kg with fortified hay in the supplementation period. The total solids content of 10.52 ºBrix was superior to the adaptation period of 10.30 ºBrix and control with 10.05 ºBrix. Meanwhile, total solids between supplements were 10.19 ºBrix with fortified hay and 10.39 ºBrix with concentrate.